White on white - Savaş, Ayşegül (Riverhead Books, 2021)
"A new novel from the author of Walking On the Ceiling, about a woman coming undone"--
Keywords: Art students / Fiction; Painters / Fiction; Creative ability / Fiction; Mental illness / Fiction; Étudiants en art / Romans, nouvelles, etc; Peintres / Romans, nouvelles, etc; Créativité / Romans, nouvelles, etc; Maladies mentales / Romans, nouvelles, etc; FICTION / Women; FICTION / Friendship; FICTION / World Literature / Turkey; Art students; Creative ability; Mental illness; Painters; Women; Gender identity; Intergenerational relationships; Psychological fiction; Fictional Work; Fiction; Novels; Romans